The Divine Name in Early Judaism: Use and Non-Use in Aramaic, Hebrew, and Greek - Meyer, Anthony (My University, 2017)
During the Second Temple period (516 BCE–70 CE) a series of developments contributed to a growing reticence to use the divine name, YHWH. The name was eventually restricted among priestly and pious circles, and then disappeared. The variables are poorly understood and the evidence is scattered. Scholars have supposed that the second century BCE was a major turning point from the use to non-use of the divine name, and depict this phenomenon as a linear development. Many have arrived at this position, however, through only partial consideration of currently available evidence. The current study offers for the first time a complete collection of extant evidence from the Second Temple period in Aramaic, Hebrew, and Greek in order answer the question of how, when, and in what sources the divine name is used and avoided. The outcome is a modified chronology for the Tetragrammaton’s history. Rather than a linear development from use to avoidance, the extant evidence points to overlapping use and non-use throughout most of the Second Temple period.
Keywords: Early Judaism, Tetragrammaton, Divine Name, Titles, Epithets